1995
DOI: 10.1021/jm00026a010
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimalarial Activity of Chalcones and Their Derivatives

Abstract: A series of chalcones and their derivatives have been synthesized and identified as novel potential antimalarials using both molecular modeling and in vitro testing against the intact parasite. A large number of chalcones and their derivatives were prepared using one-step Claisen-Schmidt condensations of aldehydes with methyl ketones. These condensates were screened in vitro against both chloroquine-sensitive and chloroquine-resistant strains of Plasmodium falciparum and shown to be active at concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
254
1
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(264 citation statements)
references
References 23 publications
6
254
1
3
Order By: Relevance
“…21 For the biochemical evaluation against T. cruzi cruzain, the highly purified enzyme (0.64 nM) in 50 mM sodium phosphate, 100 mM sodium chloride, 5 mM EDTA, pH 6.5, containing 5 mM DTT, was incubated with the compounds (chalcones 1-33 and hydrazides 34-40, Table 1) for 5 min at room temperature followed by the addition of the fluorogenic substrate Z-Phe-Arg-AMC. 22 Fluorescence was monitored on a Wallac 1420-042 PerkinElmer spectrofluorometer and measurements were done using 355 nm as the excitation wavelength and 460 nm as the emission wavelength, as previously described. 10 Cruzain activity was measured as an increase of fluorescence intensity of liberated aminocoumarin when Z-Phe-Arg-AMC was used as the substrate.…”
Section: General Procedures For the Synthesis And Purification Of N´-smentioning
confidence: 99%
“…21 For the biochemical evaluation against T. cruzi cruzain, the highly purified enzyme (0.64 nM) in 50 mM sodium phosphate, 100 mM sodium chloride, 5 mM EDTA, pH 6.5, containing 5 mM DTT, was incubated with the compounds (chalcones 1-33 and hydrazides 34-40, Table 1) for 5 min at room temperature followed by the addition of the fluorogenic substrate Z-Phe-Arg-AMC. 22 Fluorescence was monitored on a Wallac 1420-042 PerkinElmer spectrofluorometer and measurements were done using 355 nm as the excitation wavelength and 460 nm as the emission wavelength, as previously described. 10 Cruzain activity was measured as an increase of fluorescence intensity of liberated aminocoumarin when Z-Phe-Arg-AMC was used as the substrate.…”
Section: General Procedures For the Synthesis And Purification Of N´-smentioning
confidence: 99%
“…13 Diphenyl propenones (chalcones), however, also exhibit antimalrial activity, 7,14−22 and malaria trophozoite cysteine protease has been proposed as possible target for this class of compound. 14,18 Phenyl urenyl chalcones also exhibit antimalrail activity via multiple mechanisms. 7 Inspired by the above facts we thought to design and synthesize compounds based on sugars having C-linked phenyl propenone moiety and diphenyl urea units together to get hitherto unreported antimalarial agents (Figure 1).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Moreover, these compounds are known to be transformed into other compounds in a number of ways, many of which are biologically active heterocycles. [8][9][10][11] Macrocycles incorporating more than one chalcone moiety have great potential in generating new compounds suitable for molecular recognition [12][13][14][15] and photophysical 16,17 studies.…”
Section: Introductionmentioning
confidence: 99%
“…It was our consideration that if it is possible to bring about the second step of the reaction in the same pot, any target compound of the series 4 with m=n may be reached readily (Scheme 3). With this synthetic planning, 6 was refluxed separately with each of the α,ω-dibromoalkanes, Br-(CH 2 ) 2 -Br, Br-(CH 2 ) 3 -Br, Br-(CH 2 ) 4 -Br and Br-(CH 2 ) 5 Br in dry acetone with K 2 CO 3 using the reactants at the concentration 0.067 mol/L. It was observed that reaction took place in last three of these cases yielding nonphenolic products.…”
Section: Introductionmentioning
confidence: 99%